Production of afucosylated antibodies in CHO cells by coexpression of an anti‐FUT8 intrabody. Issue 8 (14th May 2022) - Joubert, Simon; Guimond, Julie; Perret, Sylvie; Malenfant, Félix; Elahi, S. Mehdy; Marcil, Anne; Parat, Marie; Gilbert, Michel; Lenferink, Anne E.G.; Baardsnes, Jason; Durocher, Yves
Abstract: Some effector functions prompted by immunoglobulin G (IgG) antibodies, such as antibody‐dependent cell‐mediated cytotoxicity (ADCC), strongly depend on the N‐glycans linked to asparagine 297 of the Fc region of the protein. A single α‐(1, 6)‐fucosyltransferase (FUT8) is responsible for catalyzing the addition of an α‐1, 6‐linked fucose residue to the first GlcNAc residue of the N‐linked glycans. Antibodies missing this core fucose show a significantly enhanced ADCC and increased antitumor activity, which could help reduce therapeutic dose requirement, potentially translating into reduced safety concerns and manufacturing costs. Several approaches have been developed to modify glycans and improve the biological functions of antibodies. Here, we demonstrate that expression of a membrane‐associated anti‐FUT8 intrabody engineered to reside in the endoplasmic reticulum and Golgi apparatus can efficiently reduce FUT8 activity and therefore the core‐fucosylation of the Fc N‐glycan of an antibody. IgG1‐producing CHO cells expressing the intrabody secrete antibodies with reduced core fucosylation as demonstrated by lectin blot analysis and UPLC‐HILIC glycan analysis. Cells engineered to inhibit directly and specifically alpha‐(1, 6)‐fucosyltransferase activity allows for the production of g/L levels of IgGs with strongly enhanced ADCC effector function, for which the level of fucosylation can be selected. The quick and efficient method described here should have broad practical applicability for the development of next‐generation therapeutic antibodies with enhanced effector functions. Abstract : Therapeutic antibodies with reduced Fc‐glycan core fucosylation show significantly increased effector functions. Joubert and coworkers present an approach where FUT8 α(1, 6)‐fucosyltransferase catalytic activity is blocked by an intrabody which is composed of an anti‐FUT8 scFv fused to a transmembrane domain of an ER/Golgi‐resident protein to promote its colocalization and interaction with the FUT8 enzyme. Upon coexpression of a therapeutic antibody with the intrabody, the secreted antibody shows significantly reduced core fucosylation.